(untitled) (Baghdad Science Journal, 2015)
A developed model has been put for the hypothesis of capturing moons in explaining the origin of Jupiter moons, and study the change of the orbital properties of these satellites as well as the distance from the planet. Jupiter moons were divided into two types according to their physical and orbital properties, they are the moons , which are formed from the same material as the planet, so it was named the original moons ,while the moons that have been captured from the surrounding space was renamed exotic moons . And the moons of exotic origin asteroid belt and the Kuiper belt in the region which is behind Neptune, the origin of each clique of moons is an asteroid fragmented after colliding previously with another body and then gathered again by simple gravity of its parts among them, and then it has been disintegrated once again due to the influence of the gravity of the planet against it, and the process of captivity are due to the gravitational interaction between the asteroid or comet and the planet when one of them enters within Hill ball to Jupiter.